New Village Law and Effectiveness of Village Government in Indonesia - Irawan, Nata; Andi Gani, Prof. Dr. Yuli; *, Dr. Suryadi; Fefta Wijaya, Andi (IJRDO - Journal of Social Science and Humanities Research, 2017)
Law 6/2014 on Village in Indonesia is a great affirmative policy, which gives recognition to villages existense, and increases authority of village governments. Using quantitative methods, research gains results that implementation of Law 6/2014 has positive influences to effectiveness of village government. Factually, village officials are already qualified to understand the act clearly and consistently. Increasing effectiveness of villages government organizations is affected by increasing of village officials training, village officials capacity, availability of resources, support of socio-economic environment, and support of organizations within the village.